(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the representation of the lyrical hero’s character in journalistic lyricism, using the poetry of G. Dáwletova, O. Saparova, and B. Seytaev as examples.